Propuesta urbana - arquitectónica como solución a la fragmentación generada por la infraestructura ferroviaria en la Ciudad de Riobamba - Barragán Torres, Cristian Iván (2024)
There is a glaring absence of public space in Riobamba City, which hinders social contact and hinders the emergence of a civic identity through encouraging unplanned meetings. The railway axis of Riobamba, which runs between "Carabobo" and "José De Pindo" streets and serves as a link line from the north to the city center, is designated as the study area for this research project. To establish intervention strategies that offer solutions to the issues of the urban network, public space, urban greenery, mobility, and urban facilities, among other issues, the research is supported by the data collected on site because of the urban and historical analysis. Urban pieces are obtained by identifying similarities of the blocks that comprise the sector. The proposal establishes general guidelines set a general mass plan, which is worked on at different scales of intervention (macro, meso and micro), the proposal frames the use of the train not only as a means of tourism, but also as a means of urban mobility, promoting different types of mobility, mainly pedestrian mobility and the use of bicycle lanes to reduce the use of automobiles, finally the intervention in vacant lots to generate public spaces and activities for common use. The proposal also frames the intervention of section 2 from “Monseñor Proaño” Avenue and “Agustín Guerrero” (micro scale), seeking the integration of public space, the connection between blocks and the integration of the railway axis through economic, cultural and sports activities. Finally, the research promotes the reactivation of urban areas using the railway infrastructure as a tool to promote positive impact in underutilized areas or areas in the process of consolidation and in this way improve the quality of social life in this sector.